Coordination of renewable energy remuneration schemes through information exchange - Thilo Grau; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The increasing scale and dynamics of the global market for renewable energy technologies has often resulted in unexpected high deployment volumes in EU Member States. These deployment peaks were particularly strong for solar photovoltaic (PV) technologies in countries using feed-in tariff remuneration mechanisms. In this paper, we develop an analytic model to capture the interactions of national remuneration schemes with the global market. The model covers two countries and one global technology market. We calibrate the model for the impact of coordinated tariff adjustments based on the experience with PV in Germany and the UK. We then use the model to measure the impact of different global module supply functions, national installation price reductions, and specific shocks on deployment effectiveness in terms of reaching national or aggregated target corridors for separate and coordinated feed-in tariff adjustment mechanisms. The relevance of the insights for wind energy technologies is evaluated. Based on the results, we discuss the implications for the coordination of remuneration schemes.
Keywords: D78; L94; O3; 330; renewable energy; feed-in tariff; coordinated remuneration schemes